Academic Tourism as an Emerging Tourism Industry in Kazakhstan - ALTYNBASSOV, Bakhyt; BAYANBAYEVA, Aigerim; ISSABEKOV, Baurzhan; BARLYKOV, Yerbolat; AKHMETOV, Bekmukhan; ZHANKUBAYEV, Bakhytbek; SHOKHANOVA, Indira (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
The purpose of this study is to investigate the development of academic tourism in Kazakhstan in recent years. Analytical papers and expert reports from the UN World Tourism Organization and a review of studies over the past two decades have been useful in determining the meaning of academic tourism and academic mobility. In addition, international and national tourism policy and regulatory acts were analyzed, reflecting the prospects of the tourism industry. Using a thematic analysis method, this study analyzed the development of academic tourism in Kazakhstan as an emerging tourism sector over the past few years. The new tax preferences, the approval of a special economic zone in priority areas provided by the Government were found as the greatest opportunity in facilitating academic tourism in the southern region of Kazakhstan. In this regard, the establishment of international university campuses can play a significant role. It is expected that the implementation of this idea will help to attract thousands of students and academics from neighboring countries and can become a real impetus for the development of tourism. Furthermore, it can positively influence other tourism sectors such as MICE tourism, eco-tourism.